Kunstgeschichte der digitalen Bilder - Maria Männig (Zeitschrift für digitale Geisteswissenschaften)
What does it mean to practice art history with digital images? In the sense of Malraux, it would then be designated the history of the digitalisable. This essay explores how medial innovations influence the perception of the past and characterise this process as a feedback phenomenon. Modifications of the artistic canon are the consequences. These questions of canon are relevant for the discipline in as far as it orients itself to the currently valid definition of art. The utopia of a decanonisation or even a general availability of knowledge is closely linked to the idea of research based on data. In response to the core problem of the relationships expressed in this speech between digital and classical humanities, the concept of mechanical agency was introduced, which describes the interaction between human and computer-based acts. In addition to contemplation moored more strongly in media theory, this essay proposes to reopen foundational debates, such as on the relationship between visual culture and art history. With a view to the history of the discipline and in light of the digital turn, this essay advocates for stronger reflection on the concepts of knowledge, work-image-art and canon, as well as on the corresponding (digital) instruments as units that are not neutral.